ECONOMIC STUDY OF CALCULATION THE WATER FOOTPRINT AND VIRTUAL WATER FOR IRAQ’S IMPORTS FROM WHEAT AND RICE DURING 2000-2020 - Jeehan.O.K.A.; B.H.H.Al-Badri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The study was aimed to identify the concepts of water footprint and virtual water and how these two concepts could be used to achieve water savings at the local level to meet the water supply deficit in Iraq,which is expected to increase in the coming years through studying the water footprint and virtual water and their impact on the foreign trade for wheat and rice crops during the period 2000-2020 and estimating the most important indicators of virtual water and the water footprint of the study crops due to the importance of these criteria in determining the amount of increase or decrease in the area of ​​the studied crops.According to the foreign trade policy.This study was concluded that the average total water footprint of the wheat and rice crops during the study period is 20.27,13.89 billion m3 respectively,and the average percentage of dependence on external water resources for both crops are 20.49%,67.98% respectivly, and the average percentage of self-sufficiency in water resources are 79.51%,32.01%respectivly,and the average unit productivity of irrigation water for both crops is 0.19,0.10 kg/m3 respectivly during 2000-2020.The average for the water needs of wheat and rice crops during the study period were 6.04,10.19 m3/kg respectivly,the average amounts of water used in local production for both crops are 14.23,4.01 billion m3 respectivly,the average amounts of virtual water imported for both crops are 6.19,10.03 billion m3 respectivly,and the average value of the imported virtual water for both crops is 382,529 thousand dollars during the period 2000-2020.